Biological Co-existence of the Microalgae – Bacteria System in Dairy Wastewater using photo-bioreactor - Ibrahim, Arwa Raad; Abdulmajeed, Basma Abbas (Iraqi Journal of Chemical and Petroleum Engineering, 2018)
Aeration system in the cultivation of Chlorella Sp. Microalgae using dairy wastewater as culture media was addressed in the current study. This research aimed to study the effect of aeration in the bubble column bioreactor on the biological synergy between microalgae and bacteria if they are present in the same place. The results show that the sterilization stage is not the dominant step in the success of microalgae cultivation in water-rich organic waste. There is a clear convergence between the growth rate of Chlorella microalgae in the sterilized and non-sterilized culture media, which gives realism if the proposal is applied industrially. Through the information obtained the aerobic bacteria in the non-sterilized media, with free of algae, are able to consume all dissolved oxygen within a very short period of time. The aeration factor is, therefore, important in that case. However, the experiments show that co-existence of bacteria and microalgae can occur even if there is no aeration system.   Consequently, the microalgae in the dairy wastewater are capable of preserving the environment of cultivation. The gases produced due to metabolic processes in bacteria or microalgae remain in solution for a certain period and are not easily removed, especially if the solution is exposed to intermittent sparging. Thus, this will give enough time for both microorganisms to consume those gases. However, the results show that the sparging system for 15 minutes and three times a day improves biomass production by 60%. Therefore, the cultivation of microalgae in addition to its desired goal can play an important role in the dairy wastewater treatment units by maintaining the appropriate environment for aerobic bacteria even in the absence of an aeration system.